Kedudukan Hukum Anak Korban Perkosaan Perspektif Undang-Undang Nomor 35 Tahun 2014 Tentang Perlindungan Anak dan Maqashid Syariah (RechtJiva, 2025)
The ratification of Government Regulation No. 28 of 2024 concerning Health promulgated in LN.2024 / No. 135, TLN No. 6952, this has received many pros and cons responses among the public regarding the rules of abortion practice. The purpose of this study is to determine the legal position of children of rape victims from the womb until they are born after the enactment of government regulation number 28 of 2024 concerning health. This research is a normative juridical research using a legislative approach and conceptual approach. The sources of legal materials used consist of three legal materials, namely, primary, secondary, and tertiary. Collection of legal materials in the form of literature studies and analysis of legal materials using prescriptive analysis techniques, namely describing primary legal materials and secondary legal materials then given an evaluation, interpreted and documented. The method of processing legal materials with five stages, namely, editing, grouping legal materials, examining legal materials, analyzing legal materials, and conclusions. The results in this study show that children in the womb and female victims of rape get a position as legal subjects, namely the same right to life and get the same rights until the child is born, as regulated in Law Number 35 of 2014 concerning Child Protection promulgated in LN.2014 / No. 297, TLN No. 5606, that a child has received several rights including the right to live, grow, develop, and participate optimally in accordance with the dignity of humanity and children's rights are human rights. In this case the child in the womb needs to get legal protection like a child who has been born, namely, entitled to inheritance from the heir (father), the condition is that the child must be born alive, if he dies when he is born, then the child is never considered to exist and will not get inheritance. Meanwhile, when viewed from maqashid sharia, a child has the right to live, grow and develop, equal justice, equality, get care and maintenance, and children in the womb do not get inheritance rights until they are born alive.